Step intervals and arterial pressure in PVS schemes - Turner,HCM; Chizari,H; Lupu,E (Institution of Engineering and Technology, 2018)
We build upon the idea of Physiological Value Based Security schemes as a means of securing body sensor networks (BSN). Such schemes provide a secure means for sensors in a BSN to communicate with one another, as long as they can measure the same underlying physiological signal. This avoids the use of pre-distributed keys and allows re-keying to be done easily. Such techniques require identifying signals and encoding methods that can be used in the scheme. Hence we first evaluate step interval as our physiological signal, using existing modular encoding method and our proposed learned partitioning function as the encoding methods. We show that both of these are usable with the scheme and identify a suitable parametrisation. We then go on to evaluate arterial blood pressure using our proposed learned mean FFT coefficients method. We demonstrate that with the correct parameters this could also be used in the scheme. This further improves the usability of PVS schemes, by identify two more signals that could be used, as well as two encoding methods that may also be useful for other signals.